Impact of wrong sexual behavior on adolescent development : a factor dragging the society towards ruin - S. Adiaha, Monday; E. Abolarin, Elizabeth; E. Orji, Uzoaku; I. Udom, Grace; Mary, Ndifon; I. Anabe, Momoh; U. Ocheje, David; Auwalu, Saminu (International Journal of Scientific World, 2017)
Impact of wrong sexual behavior of adolescent has been surveyed. It effect on the victims has been proven negative, with consequences like health effect including financial effect been a drawback, acting like a barrier to the ideal development of an individual adolescent. Wrong sexual behavior has been found to be on the increase, forcing adolescents to drop-out of school, exhibiting behaviors that do not conform to the development of the society. Result of this research findings shows the impact of wrong sexual behavior to include: Disregard for cultural/societal moral values, teenage/adolescent pregnancies, rapid increase in STDs and HIV/AIDS transmission, eagerness to practices illicit sexual acts, wrong conception about the opposite sex including sexual intercourse addiction with prostitution tendencies. The high positive percentages achieved from statistical analysis (respondent view-point) presents these impact as been on the increase, capable of dragging the society towards ruin. Recommendations of this study presents a view that the problem of adolescent wrong sexual behavior can be control , presenting guides like proper guidance and counseling , proper monitoring, aggressive sex education, reawakening of traditional African moral and value teachings, inclusion of sex education in religious teachings including proper dressing and restricting of adolescents from pornographic materials.